POTENSI DAN TANTANGAN PEMBELAJARAN DI ERA INDUSTRI 4.0 DALAM DUNIA PENDIDIKAN - Iqbal, Iqbal; Suryana, Nina; Fahrizal, Fahrizal (Dharmas Education Journal (DE_Journal), 2024)
Potential and Challenges of Learning in the Industrial Era 4.0 in the World of Education. The Industrial Era 4.0 presents various advanced technologies such as artificial intelligence (AI) and the Internet of Things (IoT) which are changing learning and teaching methods in the world of teaching. The aim of this research is a) to determine the Learning Potential in the Industrial Era 4.0 in the World of Education, b) to determine the Challenges of Learning in the Industrial Era 4.0 in the World of Education. This research uses a qualitative approach with a case study method. Interview Data Collection Techniques and Literature Study. Data analysis This research uses thematic analysis, namely: data collection, reading and understanding data, data interpretation and analysis, data verification and conclusions. The results of this research show that the majority of teachers feel the benefits of using artificial intelligence (AI) technology and digital learning platforms that allow adapting lesson material to individual student needs. Teachers report that they can provide real-time feedback based on data collected through Internet of Things (IoT) devices or learning applications. This helps students learn at their own pace and learning style, increasing engagement and retention of information. The results of this research indicate that limited technological infrastructure is the main obstacle in implementing learning technology. Teachers in rural areas or schools with limited resources revealed that they experienced difficulties in accessing digital devices and adequate internet connectivity. These limitations hinder efforts to implement technologies like AI, IoT effectively